Integrating Community-Based Approaches into National Disaster Management Policies: Lessons from Recent Natural Disasters - Kristian, Indra; Fajar Ikhsan, O.K. Mohammad (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The purpose of this research is to explore the integration of community-based approaches into national disaster management policies, using lessons learned from recent natural disasters. This study addresses the growing phenomenon of natural disasters and the limitations of existing national policies in effectively managing these crises. Employing a mixed-methods approach, including qualitative case studies and quantitative data analysis, the research identifies the strengths and challenges of community-based disaster management (CBDM) strategies. Key findings highlight the effectiveness of CBDM in enhancing community resilience and the critical need for policy integration to bridge gaps between national frameworks and local practices. The analysis reveals that integrating CBDM into national policies can significantly improve disaster preparedness and response, fostering greater community engagement and tailored solutions. In conclusion, this study underscores the practical and theoretical impact of integrating community-based approaches, suggesting that a more inclusive and adaptive policy framework can lead to more robust disaster management outcomes.